Komparasi Metode Eye Tracking dan Kuesioner untuk Usability Testing Flight Information Display System (FIDS): - Pradana, Andrianto Gusti; Wicaksono, Mahad (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to compare several methods such as eye tracking and questionnaires to find out how effective and efficient the display on the flight schedule is or what is called the Flight Information Display System (FIDS) at Juanda Airport. To see the quality of FIDS, it is necessary to evaluate with usability testing. there is standardization regarding usability testing with ISO 9241 11 which is an international standard using usability testing by measuring effectiveness and efficiency. eye tracker in evaluating usability testing by detecting the user's position, how long and the order to view. The researcher aims to evaluate and analyze the results of usability testing to respondents when doing user tasks. The test using eye tracking is carried out by testing through several test scenarios that are shown to the user, the test results will be recorded. From these tests obtained data that will be included in several usability factors that adopt ISO 9241-11, namely effectiveness and efficiency. Currently the use of eye tracking is also still unknown level of success. then there must be a comparison method of data from eye tracking results in comparison with data from questionnaires. the stages carried out during testing are need initiation, pre-user testing, user testing and post-testing analysis. Keywords: Flight Information Display System (FIDS), eye tracking, usability testing